2011
DOI: 10.1097/01.pra.0000407968.57475.ab
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder with Psychotic Features May Lead to Misdiagnosis of Dementia

Abstract: Major depressive disorder (MDD) with psychotic features is relatively frequent among patients with greater depressive symptom severity and is associated with a poorer course of illness and more functional impairment than MDD without psychotic features. Multiple studies have found that patients with psychotic mood disorders demonstrate significantly poorer cognitive performance in a variety of areas than those with nonpsychotic mood disorders. The Mini Mental State Examination (MMSE) and the Dementia Rating Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…However, our findings are also consistent with literature describing marked improvement of cognitive function in some of these patients (Pier et al, 2012;Wagner et al, 2011), as the cognitive course within the group differed markedly. CIND patients who reverted to normal might have been among those whose cognitive function was temporarily impaired by major depression (McClintock, Husain, Greer, & Cullum, 2010); thus, their baseline performance on the standardized neuropsychological tests did not reflect their cognitive abilities in remission.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, our findings are also consistent with literature describing marked improvement of cognitive function in some of these patients (Pier et al, 2012;Wagner et al, 2011), as the cognitive course within the group differed markedly. CIND patients who reverted to normal might have been among those whose cognitive function was temporarily impaired by major depression (McClintock, Husain, Greer, & Cullum, 2010); thus, their baseline performance on the standardized neuropsychological tests did not reflect their cognitive abilities in remission.…”
Section: Discussionsupporting
confidence: 94%
“…Cognitive impairment in the elderly often persists after efficacious treatment of the depression (Bhalla et al, 2009;Butters et al, 2008;Nebes et al, 2003). However, in some individuals, indications of severe cognitive impairment at the baseline are not present after a course of ECT, if remission was achieved (Pier, Briggs, Pasculli, & Kellner, 2012;Stoudemire, Hill, Morris, & Dalton, 1995;Stoudemire et al, 1991;Wagner, McClintock, Rosenquist, McCall, & Kahn, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…At baseline, indications of mild cognitive impairment were found in 27 (41.5%) patients, whereas 15 (23.1%) were no longer categorized as impaired after the ECT course. Similarly, a misdiagnosis of dementia has been reported in elderly patients with MD before they were successfully treated with ECT (Pier et al, 2012;Wagner et al, 2011). However, several studies have demonstrated that despite the improvement observed in some patients after treatment (Dybedal et al, 2015), cognitive functioning remained impaired at the group level in elderly depressed patients who presented with cognitive impairment at baseline (Butters et al, 2000;Sarapas et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Our report corroborates a study demonstrating that ECT may produce long-term cognitive improvement, 4 as well as a report questioning the validity of the Dementia Rating Scale and MMSE in assessing patients with comorbid psychotic depression and cognitive impairment. 5 …”
mentioning
confidence: 99%